Children with Psychogenic Nonepileptic Seizures - Aisha Gillan; Safiullah Shareef (Pediatric Neurology Briefs Publishers, 2019)
Researchers from the Pediatric Health Information System hospital network analyzed a large multicenter retrospective cohort to determine differences in demographics, clinical characteristics, testing, treatment and healthcare use between children ages 8-20 with epilepsy (n=13,241) and children with psychogenic nonepileptic seizures (PNES) secondary to conversion disorder (n=399).